China's Economic Evolution: From WTO Accession to Global Leadership - Yao, Suqing (Pacific International Journal, 2024)
This study provides a comprehensive exploration of the transformative journey of China's economic policies and global engagement from its accession to the World Trade Organization (WTO) in 2001 to the present day. The analysis spans three distinct phases: the initial shift from a centrally planned to a market-oriented system, the full integration into the global economic system marked by meticulous adherence to WTO commitments, and the subsequent era characterized by the Belt and Road Initiative and high-quality development strategies. Examining key milestones such as the establishment of free trade zones, internationalization of the yuan, and participation in significant agreements like the Regional Comprehensive Economic Partnership (RCEP) and the China-EU Comprehensive Agreement on Investment (CECAI), the study highlights China's pivotal role in shaping global economic structures. The findings underscore China's commitment to opening-up, fostering international cooperation, and contributing significantly to reshaping the global economic landscape.